“Sempre involta nelli sacri libri e nelle cose di Platone e di Aristotele”: Sister Felice Rasponi da Ravenna between philosophy of love and querelles des femmes - Carinci, Eleonora (Itinerari, 2023)
Felice Rasponi (1522-1579), forced by her family to enter the Benedictine convent of Sant’Andrea Maggiore in Ravenna, was known for her beauty and erudition. She published two printed works during her lifetime, the Ragionamento sopra la cognition di Dio (ca. 1570) and the Dialogo dell’eccellenza dello stato monacale (1572). She also left a manuscript autobiographical dialogue, the so-called Vita della Madre donna Felice Rasponi (ca. 1572). In the Dialogo and in the Vita Rasponi deals in different but complementary ways with the controversial topic of the two possible opportunities for a woman of her time, marriage and convent. The contribution examines the evolution of Rasponi’s thought, considering her readings and the cultural relations entertained through the convent’s parlour. In particular, it will analyse Rasponi’s use of 16th-century treatises on love in her writings, especially Leone Ebreo’s Dialoghi d’amore, and Girolamo Ruscelli’s Lettura sopra un sonetto dell’illustrissimo Signor Marchese della Terza alla Marchesa del Vasto, which she uses extensively in the Dialogo, together with other more predictable sources, to demonstrate that the union with God is the most perfect form of love.